Description Of Growth Of Devotion In Public Health Tanete Bulukumba District - Andi Nurlaily; Kurniati, Ely (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
Very rapid growth and development occur at the age of five, known as the golden age phase, therefore this phase is a very important period in terms of growth and development. The purpose of this study was to determine